A prospective randomized controlled double blinded interventional study to compare post operative analgesia using sequential intrathecal injection of fentanyl at different rates with hyperbaric bupivacaine in lower segment caesarean sections - Nelwin J Sabu; Harpreet Kaur; Veena Shukla; Harsh K Harsh; Ravi Pareek; Ekta Rani (Journal of Obstetric Anaesthesia and Critical Care, 2024)
Background: This study compared rapid and slow intrathecal fentanyl injection followed by a slow injection of bupivacaine to estimate the duration of postoperative analgesia in lower-segment caesarean sections (LSCS). Methods: The study was performed on 60 parturient aged 18-35 years undergoing LSCS and was divided equally into two groups. Group A (Normal Sequential) received slow sequential intrathecal injections of fentanyl and hyperbaric bupivacaine and Group B (Rapid Sequential) received a rapid intrathecal injection of fentanyl followed by a slow injection of hyperbaric bupivacaine. We compared the duration of postoperative analgesia, time of onset of sensory and motor block attained, the highest level of sensory block attained, duration of motor block, Visual Analogue Scale (VAS) scores, spinal anaesthesia-related complications and haemodynamic parameters between both the groups. Results: The duration of postoperative analgesia was longer (P < 0.001) in group B (3.22 ± 0.66 hrs) as compared to group A (2.53 ± 0.41 hrs.) The onset of sensory block was faster (P < 0.001) in group B (1.01 ± 0.29 min) as compared to group A (1.32 ± 0.08 min). More patients in group B achieved higher levels of sensory blockade as compared to group A (5 patients in group A and 12 patients ofgroup B achieved a sensory block up to the T2 dermatome). VAS scores and the requirement of rescue analgesia were significantly lower (10 in group B and 19 in group A). Conclusion: Rapid sequential intrathecal injection of fentanyl and hyperbaric bupivacaine provided better anaesthesia and postoperative analgesia than the normal group.